Social connectedness and life satisfaction: Comparing mean levels for 2 undergraduate samples and testing for improvement based on brief counseling. Issue 8 (16th November 2016) - Blau, Gary; DiMino, John; DeMaria, Peter A.; Beverly, Clyde; Chessler, Marcy; Drennan, Rob
ABSTRACT: Objectives : Comparing the mean levels of social connectedness and life satisfaction, and analyzing their relationship for 2 undergraduate samples, and testing for an increase in their means for a brief counseling sample.Participants : Between October 2013 and May 2015, 3 samples were collected: not-in-counseling (NIC; n = 941), initial counseling session (ICS; ie, triage session only; n = 168), and brief counseling (BC; ie, median of 4 additional counseling sessions; n = 28).Methods : Online surveys measuring demographic and background control variables, social connectedness, and life satisfaction.Results : NIC students exhibited higher social connectedness and life satisfaction than ICS students. Social connectedness significantly explained life satisfaction beyond controlled-for variables for both samples. There was a significant increase in social connectedness and life satisfaction for the BC sample.Conclusions : Social connectedness is an important antecedent of life satisfaction for undergraduates. Brief counseling can increase transition students' social connectedness and life satisfaction.